El control interno en los departamentos de facturación y bodega y su incidencia en la gestión administrativa de la empresa Relco S.C. periodo 2012 - Guatumillo Chuez, Mayra Alexandra (2013)
This research was conducted at the Company "RELCO SC", located in Canton Quevedo, province of Los Rios, the miry Sector. The investigation lasted six months and focused on the evaluation of the internal control system specifically in the areas of warehouse and company sales. The work began with the diagnosis of the situation in the place of practical facts, deducing how and why the company is working in the way as it has done, for which they proceeded to use interview guides staff administrative. The following analysis was performed for achieving determine that the number of interviews most people say that if there are shortcomings in various departments such as billing and cellar. Because of the importance of their activities raised implementing a functional program is administered, manage and organize the activities of entry and exit of goods properly, this instrument is the answer to the problems of the company also added to draft a training plan for all administrative and operational staff who have to receive a competitive approach both internally and externally, optimizing organizational performance and business of it.